Clustering of IRE1α depends on sensing ER stress but not on its RNase activity. Issue 9 (14th June 2019) - Ricci, Daniela; Marrocco, Ilaria; Blumenthal, Daniel; Dibos, Miriam; Eletto, Daniela; Vargas, Jade; Boyle, Sarah; Iwamoto, Yuichiro; Chomistek, Steven; Paton, James C.; Paton, Adrienne W.; Argon, Yair
ABSTRACT: The sensors of the unfolded protein response react to endoplasmic reticulum (ER) stress by transient activation of their enzymatic activities, which initiate various signaling cascades. In addition, the sensor IRE1α exhibits stress‐induced clustering in a transient time frame similar to activation of its endoRNase activity. Previous work had suggested that the clustering response and RNase activity of IRE1α are functionally linked, but here we show that they are independent of each other and have different behaviors and modes of activation. Although both clustering and the RNase activity are responsive to luminal stress conditions and to depletion of the ER chaperone binding protein, RNase‐inactive IRE1α still clusters and, conversely, full RNase activity can be accomplished without clustering. The clusters formed by RNase‐inactive IRE1α are much larger and persist longer than those induced by ER stress. Clustering requires autophosphorylation, and an IRE1α mutant whose RNase domain is responsive to ligands that bind the kinase domain forms yet a third type of stress‐independent cluster, with distinct physical properties and half‐lives. These data suggest that IRE1α clustering can follow distinct pathways upon activation of the sensor.—Ricci, D., Marrocco, I., Blumenthal, D., Dibos, M., Eletto, D., Vargas, J., Boyle, S., Iwamoto, Y., Chomistek, S., Paton, J. C., Paton, A. W., Argon, Y. Clustering of IRE1α depends on sensing ER stress but not on its RNase activity. FASEB J. 33, 9811–9827 (2019). www.fasebj.org